NOMINA BAHASA DAYAK NGAJU - Elisten Parulian Sigiro (Multilingual, 2015)
This study aims to examine how the type, category, and morphologic processes noun Ngaju Dayak language (BDNg). The method used in this research is descriptivequalitative method because the method of this study reflect the reality on the factfindings that is in the field as it is. Thus, the researchers tried to describe objectivelyand precisely the aspects nouns of BDNg in accordance with the conditions of thecurrent BDNg. Data collection is done through two techniques, ie, interviewtechniques and documentation. The findings of this study, that is syntactically, noun ofBDNg can be characterized by traits (a) does not have the potential to join the famousparticle beken 'not', (b) have the potential to be preceded by coal particles bara 'of',(c ) shall be preceded by an adverb degree somewhat (labih 'more' and tutu 'very'),and (e) may be preceded by the adverb that states the amount, as kapucuk ‘one pointand kabatang 'one a'. Based on its shape, noun of BDNg can be distinguished on thebasis nouns and nouns derived. Based on semantic aspects, BDNg noun categoriesdifferentiated into animate and inanimate nouns. Meanwhile, if viewed from the aspectof the process of forming a noun, noun BDNg can be divided into four processes,namely (a) affixation, (b) reduplication, and (c) compounding. Noun formationprocess via affixation BDNg is quite productive and allows formed on the combinationof affixes.